Play all day : design for children. - Klanten, Robert, 1964- (Berlin : Gestalten, 2009)
Design for children is ubiquitous, but the vast number of products on the market are commonplace. Play All Day documents a collection of the most vibrant, stimulating and engaging design products and concepts for children. This book sets a new standard of design for children by presenting smart products and concepts for smart parents and their kids. Play All Day presents fascinating examples of innovative and well-designed toys, playgrounds, play environments, room decorations, wall coverings, furniture and kindergarten architecture. In addition to these products, it also presents illustration, photography as well as new and original ideas offering playful solutions that talented designers and creative parents are designing for and with their kids. Play All Day: Design for Children is an inspiring reference for design-savvy parents and other professionals.